Single case research methods in sport and exercise psychology - Barker, Jamie (Routledge, 2011)
This is the first book to fully explain single-case research in the context of sport and exercise. Starting with first principles, it offers a comprehensive introduction to the single-case research process, from study design to data analysis and presentation.